The Loroxanthin Cycle: A New Type of Xanthophyll Cycle in Green Algae (Chlorophyta) - van den Berg, Tomas E.; Croce, Roberta (Frontiers in Plant Science, 2022)
Xanthophyll cycles have proven to be major contributors to photoacclimation for many organisms. This work describes a light-driven xanthophyll cycle operating in the chlorophyte Chlamydomonas reinhardtii and involving the xanthophylls Lutein (L) and Loroxanthin (Lo). Pigments were quantified during a switch from high to low light and at different time points from cells grown in Day/Night cycle. Trimeric LHCII was purified from cells acclimated to high or low light and their pigment content and spectroscopic properties were characterized. The Lo/(L+Lo) ratio in the cells varies by a factor of 10 between cells grown in low or high light leading to a change in the Lo/(L+Lo) ratio in trimeric LHCII from 0.5 in low light to 0.07 in high light. Trimeric LhcbMs binding Loroxanthin have 5±1% higher excitation energy transfer from carotenoid to Chlorophyll as well as higher thermo- and photostability than trimeric LhcbMs that only bind Lutein. The Loroxanthin cycle operates on long time scales (hours to days) and likely evolved as a shade adaptation. It has many similarities with the Lutein-epoxide - Lutein cycle of plants.